An unusual cause of cyanosis in a patient with COPD. (1st March 2013) - Chang, You-Jin; Ali, Haider; Draper, Adrian; Chua, Felix
Abstract : We present a case of acquired methaemoglobinaemia related to the prolonged use of dapsone in a patient with chronic hypoxia. The patient was initially successfully treated for infective exacerbation of chronic obstructive pulmonary disease (COPD). However, he remained persistently hypoxic on pulse oximetry despite a normal PaO2 on arterial blood gas sampling. His fraction of methaemoglobin ( F MetHb) was found to be elevated at 13%. After cessation of dapsone, his clinical cyanosis recuperated, his exercise tolerance and functional capacity improved and his F MetHb normalised to 1%.